CUSTOMER VALUE CREATION IN VOCATIONAL HIGHER EDUCATION: CASE IN INDONESIA - Jajang Burhanudin; Poniah Juliawati; Anna Noviana (Dinasti Publisher, 2020)
Vocational higher education has developed as a service that cannot avoid marketisation. One of the higher education marketing tasks is creating the value of its customers. However, the creation of customer value in vocational tertiary education has not been touched by researchers. This study aims to determine the concept and measurement of the dimensions of customer value creation in vocational higher education. In addition, it tries to measure the validity and reliability of its dimensions. This study uses analyzing the concept of customer value creation in several journals to then be associated with value creation in vocational higher education. As for the respondents were academic citizens from each institution consisting of leaders, lecturers, heads of study programs, education staff and students taken proportionally. This research has a total of 876 respondents from 30 institutions and uses a structured questionnaire based on a 7-point scale. The results showed that the creation of customer value in vocational tertiary education can be explained by all of its dimensions. Although not all indicators can explain the dimensions of customer value creation. Indicators that can explain customer value creation are changes in knowledge, general skills, special skills, learning suitability that consider student conditions and objectivity of assessment. The model is quite good with moderate predictive relevance (Q2). This research is limited to vocational higher education in the provinces of West Java and Banten. There is very little data coming from companies that use graduates. The originality of this research is customer value creation in vocational higher education consisting of three dimensions, namely learning outcomes, learning strategies, and learning evaluation.